Chemical-bromatological composition of elephant grass silage with increasing levels of acerola by-product (Research, Society and Development, 2023)
The objective of this study was to evaluate the chemical-bromatological composition of elephant grass (EG) silages with the addition of acerola by-product (ABP). The experimental design was completely randomized, with five treatments: Treatment 1 = 100% EG; Treatment 2 = 94% EG + 06% ABP; Treatment 3 = 88% EG + 12% ABP; Treatment 4 = 82% EG + 18% ABP and Treatment 5 = 76% EG + 24% ABP, with four replications (silos). EG and ABP were mixed at the time of ensiling. The silos were open at 42 days and samples were collect for chemical analysis. The addition of up to 24% of ABP in EG silage significantly (P